An evaluation of housing flexibility after seven years of habitation: IBA Hamburg 2013 - Lutolli, Blerim (Journal of Architecture and Urbanism, 2021)
Flexibility in housing has been used for a long time to meet the changing needs of inhabitants. After a century of vicissitude, flexibility became a means for architects to deal with social changes in the new millennium. The International Building Exhibition (IBA) 2013, which took place in Hamburg, Germany, is an example of how the concept of flexibility is being adopted. Housing, in particular, the post-occupancy phase, has not been studied, despite the urban-level aspects of the IBA Hamburg having been extensively written about. Seven years after its construction, nothing is known about what happened regarding these new approaches. The purpose of this study is to investigate the number of households in the IBA Hamburg housing projects that have used the promoted concept of flexibility, particularly in the “Building Exhibition within the Building Exhibition.” As a result, this article aims to shed light on this issue by presenting data from a field survey regarding whether floor plan flexibility was used, and if so, to what extent and what were the reasons. As a result, the author utilized an administered and self-administered open and closed-ended survey questionnaire research approach to collect necessary data for the execution of this investigation. The survey was conducted in twenty-two apartments, with four residential buildings chosen as a case selection for this investigation. The results of this study revealed that, despite being considered during the initial planning phase, flexibility was not commonly applied in the housing projects of IBA Hamburg 2013. Furthermore, the findings reveal that the extent of use of flexibility in these case studies is closely linked with the occupation status of the inhabitants.